IMPLEMENTATION OF E-LKPD INTEGRATED PROBLEM BASED LEARNING MODEL TO IMPROVE STUDENTS' MASTERY OF CONCEPTS AND COMMUNICATION SKILLS - Ossy, Sesria; Ulmi, Fauziah; Asrizal, Asrizal; Werina, Werina (PILLAR OF PHYSICS EDUCATION, 2024)
21st century learning requires a student-centered learning process and requires students to have knowledge and skills regarding technology, media and information, as well as having 4C skills, one of which is communication skills. Communication skills are 21st century competencies that need to be developed in the independent curriculum. The type of research conducted was classroom action research with the aim of improving students' communication skills through the implementation of an integrated E-Students Worksheet with the Problem Based Learning (PBL) model. The classroom action research model used is the Kemmis-Mc Taggart spiral model. The PTK model consists of 4 stages, namely planning, action, observation, and reflection. Class action research was conducted over two cycles of four meetings. Each meeting is carried out for 3 hours of lessons apart from daily test activities. The instrument used was an observation sheet of students' communication skills filled in by two observers during the learning process. The results of the first cycle of research obtained an average of 76 students' communication skills in the communicative category and the second cycle obtained an average of 84 in the very communicative category. This shows that the application of an integrated E-Students Worksheet with the Problem Based Learning model can improve students' communication skills.